1983
DOI: 10.1073/pnas.80.8.2221
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an intact DNA polymerase-primase from embryos of Drosophila melanogaster.

Abstract: A procedure has been devised for the purification of intact DNA polymerase a from early embryos of Drosophila melanogaster. The purified enzyme consists of at least three polypeptides with Mrs of 182,000, 60,000, and 50,000. These are related antigenically to the a (Mr 148,000), .l (Mr 58,000), and Y (Mr 46,000) subunits, respectively, of the DNA polymerase described previously [Banks, G. R., Boezi, J. A. & Lehman, I. R. (1979)J. Biol. Chem. 254, 9886-9892]. The-a subunit (Mr 182,000) has a molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(49 citation statements)
references
References 26 publications
(19 reference statements)
2
47
0
Order By: Relevance
“…dThd was a strong inhibitor of the phosphorylation of dCyd, dAdo, and dGuo with these data indicate that the four substrates are phosphorylated at the same site of the enzyme. The absence of a TK equivalent to the mammalian S-phase specific TK1 was unexpected, as other DNA replication associated enzymes previously have been isolated from Drosophila embryonic cells (25,26). Additionally, the absence of a dCK equivalent to the mammalian dCK should be noted.…”
Section: Discussionmentioning
confidence: 85%
“…dThd was a strong inhibitor of the phosphorylation of dCyd, dAdo, and dGuo with these data indicate that the four substrates are phosphorylated at the same site of the enzyme. The absence of a TK equivalent to the mammalian S-phase specific TK1 was unexpected, as other DNA replication associated enzymes previously have been isolated from Drosophila embryonic cells (25,26). Additionally, the absence of a dCK equivalent to the mammalian dCK should be noted.…”
Section: Discussionmentioning
confidence: 85%
“…They showed that Pol α consisted of four subunits; the largest, at 180 kDA, contained the DNA polymerase activity (42). Ron Conaway, a graduate student, then demonstrated that the most purified preparations of Pol α contained primase activity (primase had not yet been demonstrated in eukaryotes); he and Laurie Kaguni showed that the primase was associated with the two smaller of the four subunits (43). The association of primase with Pol α in Drosophila was quickly confirmed by several laboratories, in eukaryotes as diverse as baker's yeast and humans.…”
Section: Eukaryotic Dna Replicationmentioning
confidence: 99%
“…The subunits of pol--primase complex in the yeast Saccharomyces cerevisiae are 167, 79, 62, and 48 kDa polypeptides Biswas et al, 2003). The pol--primase complex from Drosophila melanogaster consists of 182, 73, 60, and 50 kDa subunits (Kaguni et al, 1983;Cotterill et al, 1987). The estimated roles of each subunit of pol-is summarized in Fig.…”
Section: Structure Of Pol-α-primase Complexmentioning
confidence: 99%